Angels as the Shape of Energy: How the Threshold Narratives Shaped the Meaning Construction of 'Angel' and 'Energy' in a Central and Eastern European New Religious Group. - Csáji, László Koppány (Journal of Religion in Europe, 2020)
The status-dependent access to information results in multilevel meaning construction in a charismatic Christian group. The notion of 'angel' is discursively transforming (during evangelization rituals, healing, angel visions, etc.). To acquire language skills, one may encounter and accept threshold narratives. After the notion of energy was introduced into the group (2012), former ideas ('rectangular form' and 'shape-changing kind' of angels) were intermixed with it. Energy became a general, fundamental principle, but it was not obvious how they could manage its dual kind: 'positive energy' and the evil counterpart ('spiritual/negative energy'). My argumentation is based on discourse analysis and cognitive semantics.